The Structural and Content Criticism of the Book Al-Adab Alarabi Alhadith, Madaresoho Va Fononoho Va Tatavorohi Va Qazayaho Va Namazejon Menho - Abdulali Alebooye Langrudi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Modern Arabic literature, because of its important role in transferring the contemporary culture and thoughts of Arabs, enjoys a special status in the curriculum of Arabic language and literature majors in Iranian universities. As a result, to introduce contemporary Arabic literature, various courses entitled contemporary Arabic poetry and prose have been offered at different educational levels. Besides, to achieve this goal, many books and textbooks have been written in Iran and in the Arab world. Undoubtedly, criticizing and reviewing these books is a major step in fulfilling the objectives of teaching contemporary literary texts. Therefore, the present study intends to evaluate the book Al-Adab Al-Arabi Al-Hadith; … authored by Muhammad Saleh Alshanti, using a descriptive-analytical approach. While introducing the book, the article tried to address both its strong points and weaknesses in two domains of form and content. The findings indicate that with regard to form, the book suffers from certain shortcomings such as lack of defining terms, using personal judgments in analyses, compiling rather than composing, mixing didactic and critical issues, and incoherence of literary approaches.